Simple digital speckle pattern interferometer (DSPI) for investigation of art objects - Lasyk, Łukasz; Łukomski, Michał; Bratasz, Łukasz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
Technical development and practical evaluation of a simple digital speckle pattern interferometer (DSPI) for the non-invasive, non-contact detection and characterization of early-stage damage of painted objects of art, like fracturing and layer separation, are reported. One of the most important features of the presented measuring system is a possibility to progress stepwise from the simplest version of the instrument based on the digital image correlation (DIC), to more advanced and accurate ones: DSPI for thermally- and sound-induced surface deformation. Analysis of the resonant frequency of a vibrating delaminated paint layer was, for the first time, used to detect the damage progress in polychrome wood and proved to be extremely sensitive and accurate. This method, together with two other presented in the article makes the multilevel analysis of the preservation state of the object’s surface possible and provides information on the damage on a desired level of complexity and accuracy.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 687-700
Keywords: optyka; speckle interferometry; non-destructive testing; painted wood; art objects; delamination; fracturing